Transmission Line Capacity Enhancement with Unified Power Flow Controller Considering Loadability Analysis (ELEKTRIKA- Journal of Electrical Engineering, 2019)
This paper proposes transmission line capacity enhancement with optimal location and sizing of UPFC on IEEE 14-bus network. This is necessary because of the increase in load growth with every passing day without an equivalent increase of line capacity which has brought many power systems closer to their stability limit. The dynamic and practical application of this proposed method is achieved by increasing linearly, the loading factor (Î») from 1.25 to 1.50 of the base case value of 1.0 and then, its effect is investigated. In each of the increment, the power flow result is obtained using Newton-Raphson method, while the optimal location and sizing of UPFC are done using Grey Wolf Optimization (GWO) technique. The voltage deviation before and after the installation of the FACTS device is also studied at each load variation. This approach will help the bulk dispatcher of power to plan ahead so as to meet and supply the ever-growing in the demand for adequate and reliable power system as a result of population growth, improved living standards and technological advancement. The efficacy of the proposed method is verified on a standard IEEE 14-bus system. The simulation results show the effectiveness and suitable performance of the proposed methodology at enhancing transmission capacity and deferring or eliminating for transmission line upgrading.
Keywords: Line loadability; UPFC; Grey Wolf Optimizer; Voltage Stability; Overloading